The Spread of Democracy and International Security - Muhammad, Ali (Jurnal Hubungan Internasional, 2012)
This paper rejects the determinism of the realist position. Domestic politics or the nature of the regime does influence the foreign behavior of the states, and in turn, the probability of war, peace, and international security. In supporting the liberal argument, it will be argued that the spread of democracy will contribute to the promotion of international security. The argument is based on three main reasons:first, the persuasiveness of â€œdemocratic peaceâ€ thesis, secondly, the strong evidence of the existence of the democratic peace, and, thirdly, the failure of realist critique. Following the logic, the more the states in the world become democratic, the wider â€œthe zone of peaceâ€ will emerge and the less the likely are conflicts and war among states